SCAVENGING ACTIVITIES OF RHINACANTHUS NASUTUS (L.) KURZ. LEAVES IN CHLOROFORM EXTRACT - Catherine Sheeja V2, Anami Augustus Arul A1, Blessy R2, Ani Besant S2, Hanna Jeeja Alexander2, (Chelonian Research Foundation, 2023)
Rhinacanthus nasutus (l.) Kurz was evaluated for its antioxidant activity in this study. Rhinacanthus nasutus is a member of the Acanthaceae family. Folk medicine uses it as a remedy for liver disorders, skin disorders, and other pharmacological effects. It was sought to determine the antioxidant activity of Rhinacanthus nasutus (L.) Kurz. leaf extract using DPPH assay, H2O2, NO and SOD scavenging activity methods. As compared to DPPH, Hydrogen peroxide, Nitric oxide and Sodium oxide, Rhinacanthus nasutus leaf extract exhibited better antioxidant activity against Nitric oxide.